The Representation of Postfeminism in American Consumer Culture - Habib, Meriem; Haci, Bouchra; Kaid Nassima (Faculty of Letters and Foreign Languages Department of English, 2017)
Postfeminism is a very crucial and highly debatable area of study, as it arises many confusions and questions in the minds of the American public. Those questions took place from postfeminists’ integration in the Consumer Culture which once was forbidden by early feminists mainly first and second-wave feminists. As a result, this dissertation aspires to provide key definitions to some significant concepts, in order to serve as a baseline from which the other parts of the dissertation will rely on; in addition this research paper attempts to present each wave’s points of view on consumerism, and display the reasons that pushed postfeminists to take part in this culture. Furthermore, this paper tries to highlight the link that exits between Consumer Culture and Popular Culture in order to analyze the portrayals of women and postfeminists in Popular Culture’s different forms along with depicting the different reactions of the patriarchal society and other feminist groups towards postfeminism. Eventually, this dissertation will demonstrate that those reactions are mere misunderstandings and preconceived thoughts about postfeminism, and the issues that the latter is witnessing, are part of their continuous straggle for recognition